Effects of preparing techniques and aging on dissolution behavior of the solid dispersions of NF/Soluplus/Kollidon SR: identification and classification by a combined analysis by FT-IR spectroscopy and computational approaches. (January 2015) - Li, Xiang; Jiang, Chuan; Pan, Lili; Zhang, Haoyang; Hu, Lang; Li, Tianxue; Yang, Xinghao
Abstract Context: Pharmaceutical solid dispersions are known to be seriously affected by issues of aging and processing. Objective: This study investigated the spectral patterns in the solid dispersions (SD) of Nifedipine/Soluplus/Kollidon SR and the feasibility of the methodology in identification and evaluation of the solid dispersions. Methods: The SD samples were prepared by hot melt extrusion (HMESD), solvent-evaporation (SESD), and fusion-cooling (FCSD). In order to distinguish the different SD samples, a combined analytical strategy by FT-IR spectrum, Raman spectrum, and computational approaches (PCA and HCA) were developed to investigate the spectral patterns of the solid dispersions. Differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), scanning electron microscope (SEM), and dissolution test were employed as the reference characterization. The stability test under the accelerated condition was carried out to investigate the physical stability of the SDs. Result: For the three prepared SDs, the evident differences on the dissolution behaviors and the trend of aging was observed. By means of the combined analytical strategy, the samples could be successfully identified in terms of their preparing techniques. The strength of hydrogen bonding interaction between NF and polymers decreased in the order of HMESD > SESD > FCSD. The results of the stability test indicated that the similarity factor f2 value of dissolution profile decreased in the order of HMESD > SESD > FCSD. HMESD exhibited a tendency of minimal changing on both dissolution behavior and spectral patterns. Conclusion: The combined strategy suggested the possibility for identification of specific SDs in quality control and prediction of their trends on the aging.